Persepsi Penganut Tarekat Naqsyabandiyah Tentang Hadis-Hadis Eskatologi (Studi Terhadap Jama’ah Surau “Baiturrobbi” Kelurahan Bajak Kota Bengkulu) - Rozian Karnedi; Maryam Maryam; Ashadi Cahyadi (Manhaj: Jurnal Penelitian dan Pengabdian Masyarakat, 2019)
Tarikat which the author means is a system of living together as an effort to spiritualize the practice and understanding of Islamic teachings towards the achievement of ma'riffatullah. In this perspective, operationally this formula can be understood as a collective effort in the effort of tazkiyah al-nafs. In other words tarikat can be understood as an institution of Sufism learning. The author is of the opinion that this is due to the practice of tarikats where there are teachers who are called murshid or sheikhs, and are usually accompanied by a representative called the caliph, while his followers are called students (salik), who must go through certain methods or exercises. The training ground is called rabath, zawaiyah, or taqiyah which in Persian is called khanaqah. And in West Sumatra this training ground is called surau. In addition, in the practice of the path between students and teachers there are rules, manners and certain things that must not be violated and must be obeyed. Likewise there are rules between students and friends. Based on the understanding of several key terms contained in the title of the research described above, the author can emphasize that through the title of this research, the study will explore further the perceptions of followers of the surau Baitur Rabbi in understanding the eschatological traditions.